How can Computer Aided Tolerancing support Closed Loop Tolerance Engineering? - Schleich, Benjamin; Wartzack, Sandro (Procedia CIRP, 2014)
Since geometric deviations decrease the quality and functional compliance of mechanical products, geometric variations management is an important issue for quality-aware companies in all phases of the product life-cycle. In this regard, the Closed Loop Tolerance Engineering Model highlights the main activities during geometric variations management and can be used to analyse the relations between the different involved actors. Though computer aided engineering tools are widely spread in product development practice with the aim to ease product design and analysis, these tools are mainly used separately and are not integrated in a coherent virtual geometric variations management process. Therefore, in this paper, the prerequisites for a holistic computer aided tolerancing process during product development based on the CLTE model are analysed. The main question answered is, which tolerance simulation tools are required and how should they be connected in order to enable a coherent and integrated computer-aided tolerancing process. Based thereon, important software tools are identified and drawbacks as well as main potentials for improvement are carved out. The novelty of the contribution can be found in the consideration of the geometric variations management process from a computer-aided tolerancing point of view and in addressing possible improvements for the development of software tools for a coherent and complete computer aided geometric variations management process.
UnivIS-Import:2015-04-16:Pub.2014.tech.FT.FT-KLMEFK.howcan
Keywords: Design for X; Robust Design; Product Quality